Jump for joy! [compact disc] - Babypants, Caspar (Aurora Elephant Music, 2017)
JUMP FOR JOY! is the 13th album from Caspar Babypants (aka Chris Ballew from the Seattle rock and roll band The Presidents of the United States of America) and is full of super fun sing along good time music for the whole family to enjoy together. As with all the Caspar Babypants albums, the energy on the album goes from upbeat and fun at the beginning to sleepy and mellow at the end. The hope is that the music will help engage and then relax your kids and you so that you can recharge yourselves. JUMP FOR JOY! is ready to take you on a bouncy musical trip and then drop you off in a relaxing place when you are through. Simple acoustic instruments and thoughtful arrangements will engage the kids and the parents alike so clear space for a dance floor and enjoy!